Islam di Perbatasan Indonesia-Malaysia: Potret Dakwah di Sajingan Besar, Kalimantan Barat - Imanuddin Imanuddin; Deni Irawan; Zulfikar Ghazali; Datuk Imam Marzuki (Syams: Jurnal Kajian Keislaman, 2021)
This article aims to analyze da’wa activities in Sajingan Besar, WestKalimantan. This research is field-based with qualitative methods. Dataobtained through observation, interviews, and documentary studies. Thisresearch was conducted for six months, namely: February to July 2019. Thedata obtained showed that there was a gap in da’wa methods in SajinganBesar as one of the border areas between countries. The forms of da’wafound such as: tausiyah, recitation, Friday sermons, hadrah arts, andgotong royong show that da’wa in Sajingan Besar is still carried out usingconventional methods with the support of previously established socialstructures. There have been no significant innovations, such as da’wathrough audiovisual media, philanthropy, and political approaches, and inmore interesting ways. This is due to the limitations of adequateinfrastructure for da’wa innovation in Sajingan Besar. The authorconcludes that the development gap greatly affects the development ofda’wa activities carried out in border areas between countries.